Bermain Peran â€œPelangi di Sekolahkuâ€ untuk Meningkatkan Pengetahuan Toleransi Anak Usia Prasekolah - Rusmaladewi Rusmaladewi; Wisjnu Martani (HUMANITAS: Indonesian Psychological Journal, 2014)
ABSTRACTAs an archipelago country, Indonesia has 1.128 tribes, therefore, Indonesia has a lot of cultures,Â languages, races, religions and customs. This diversity if it is not well managed, is able to be theÂ source of conflict. As the effort of preventing the conflict, since the early age of children, it is betterÂ to give them knowledge of tolerance. The objective of this research is to carry out the validation ofÂ role playing module â€œPelangi Di Sekolahkuâ€ towards the knowledge of tolerance on the early age ofÂ children particularly the kindergarten students. The participants of this research were 32 kindergartenÂ children. The participants were separated into control group (18 children) and experiment groupÂ (14 children). The hyphotesis of this research was that the role playing module â€œPelangi Di Sekolahkuâ€Â was able to improve the knowledge of tolerance on the early age of children. The method of theÂ research used untreated control group design with pretest and posttest. The result of the statisticalÂ test which used mixed anava showed that there was the significantly difference between experimentÂ group and control group with sig (0.000) < 0.01. The effective contribution of the role playing on theÂ experiment group was 79.1%.Key words : Tolerance, Role playing, Preschool Children